New Directions in Social Work Practice - Hatton, Kieron, Jr (Transforming Social Work Practice Series., 2015)
'Hatton's book is a welcome antidote to stagnation and moribund thinking in contemporary professional practice and readers will gain much from engaging with the concepts he sets out and the challenges he raises.' Jonathan Parker, Series Editor.